Diseño de un manual de control interno aplicado al manejo de los activos fijos para la compañía camaronera Ferasa S. A. en la ciudad de Guayaquil. - Torres Torres, Melba (2015)
This internal control manual establishes a methodology for the proper management and operation of fixed assets within a company. I have chosen as a particular case the Compañía Camaronera Ferasa S. A. located in the city of Guayaquil, which due to its rapid growth in recent years, employees of the same do not know about the policies and procedures related to the recognition, measurement and control of fixed assets. In the Company, there were many irregularities and deviations in the handling and processing of fixed asset transactions between major errors can cite differences in the list of fixed assets with financial statements, capitalizing assets that do not meet the recognition criteria established in the IAS 16 Property, plant and equipment, inability to physically identify the acquired fixed assets, determination of useful lives inappropriate, among others. It was designed a procedures manual, which contains all instructions and information policy responsibilities, functions, systems and procedures of the various operations or activities to be undertaken within the Compañía Camaronera Ferasa S. A. relative to fixed assets and will serve as a guide for other firms engaged in this activity.